171 Prevalence of a nice-defined indication for inclisiran in a real-world trans-pandemic acute coronary syndrome cohort. (6th June 2022) - Shaji, Nimisha; Elamin, Nadir; Nelson, Thomas; Varian, Frances; Storey, Robert; Parker, William
Abstract : Introduction: Hypercholesterolaemia is a major modifiable risk factor for acute coronary syndromes (ACS). In October 2021, the National Institute for Health and Care Excellence (NICE) recommended that the small interfering ribonucleic acid against proprotein convertase subtilisin/kexin type 9, inclisiran, be offered to certain patients, including those with a history of ACS and low-density lipoprotein cholesterol (LDL-C) level of ≥2.6 mmol/L despite maximum tolerated statin or other lipid-lowering therapy. We aimed to estimate the proportion of our recently treated ACS patients who are likely to have a NICE-defined indication for inclisiran. MethodsA systematically selected sample of records from patients treated for ACS at our centre from 2019–2021 were reviewed (n=370). Data on demographics, diagnoses, treatments and biochemistry results were collected. Proportion of patients with a NICE-defined indication for inclisiran was determined and 95% confidence interval calculated. Where required and valid, LDL-C was calculated using the Friedewald equation. Results: Patients included had a median age of 67 (IQR 58–79) and 74.1% were male. The index diagnosis was ST-elevation myocardial infarction (STEMI) in 46.2% and non-STE-ACS in 53.8%. 97.3% were receiving a statin at time of follow-up, 4.1% ezetimibe and 0.3% a fibrate. Documented reasons for statin avoidance included previous adverse drug reactions and perceived futility in extreme frailty.Post-discharge measurement of lipid profile was performed in 319 (86.2%) of the cohort. Lack of measurement appeared influenced by changes related to the COVID-19 pandemic (20.3% after March 2020 vs. 7.0% before, odds ratio [OR] 3.4, 95% CI 1.7 to 6.7, p=0.0002). There was evidence of significant improvement in lipid profile between admission and first post-discharge measurement (e.g. total cholesterol 4.8 ±1.4 vs 3.5 ±1.1 mmol/L, p<0.0001).Of those patients with a post-discharge measurement, 29 (9.1%) had LDL-C ≥2.6 mmol/L. Of these, 24 were receiving maximum intensity statin therapy whilst 2 were receiving statin but not at maximum dose. 3 were statin intolerant and receiving ezetimibe but with the potential to add another non-statin lipid-lowering drug. At least 24 (7.5%, 95% CI 4.6 to 10.4) would therefore have a clear indication for inclisiran based on current NICE guidance.A diagnosis of STEMI was associated with increased likelihood of LDL-C ≥2.6 mmol/L (OR 2.6, 1.1 to 6.1, p=0.024). No other significant relationships with other characteristics were seen. Conclusions: Based on these data, approximately 5 to 10% of patients with recent ACS treated in a typical UK centre can be expected to have an indication for inclisiran treatment. Having an accurate estimate in this population can help local resource planning and communication with primary care. We should ensure that monitoring of lipid profile after hospitalisation for ACS is not impacted long-term by the COVID-19 pandemic. Conflict of Interest: None